2015
DOI: 10.1103/physrevb.91.205141
|View full text |Cite
|
Sign up to set email alerts
|

Fractional topological insulators: From sliding Luttinger liquids to Chern-Simons theory

Abstract: The sliding Luttinger liquid approach is applied to study fractional topological insulators (FTIs). We show that FTI is the low energy fixed point of the theory for realistic spin-orbit and electronelectron interactions. We find that the topological phase pertains in the presence of interaction that breaks the spin invariance and its boundaries are even extended by those terms. Finally we show that one dimensional chiral anomaly in the Luttinger liquid leads to the emergence of topological Chern-Simons terms i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 46 publications
0
60
0
Order By: Relevance
“…Naively, one would expect either one of the relevant operators g n or g ε to overtake the marginal couplings in Eqs. (39)(40)(41) and govern the low-energy physics, leading to more conventional, long-range-ordered phases. However, the fate of the system also depends on the bare values of the coupling constants, and cases in which a marginal operator reaches strong coupling before relevant ones have been discussed in the literature 61,63,64 .…”
Section: Two-dimensional Chiral Spin Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…Naively, one would expect either one of the relevant operators g n or g ε to overtake the marginal couplings in Eqs. (39)(40)(41) and govern the low-energy physics, leading to more conventional, long-range-ordered phases. However, the fate of the system also depends on the bare values of the coupling constants, and cases in which a marginal operator reaches strong coupling before relevant ones have been discussed in the literature 61,63,64 .…”
Section: Two-dimensional Chiral Spin Liquidmentioning
confidence: 99%
“…Our approach is based on the "sliding Luttinger liquid" or "coupledwire approach" to the fractional quantum Hall effect (FQHE) 29,30 . Similar constructions based on arrays of one-dimensional (1D) subsystems have proven powerful in the description of exotic quantum Hall states and non-Abelian anyons [31][32][33][34][35][36] , fractional topological insulators [37][38][39][40] , liquids of interacting anyons 41,42 and purely 1D systems [43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…1), where each of them can be treated as a one-dimensional Luttinger liquid by bosonization [75][76][77][78][79][80][81][82][83][84][85][86]. This will allow us to introduce the Floquet version not only of TIs but also of Weyl semimetals in driven 2D systems.…”
mentioning
confidence: 99%
“…Starting with the pioneering work of Kane et al, 35,36 it has been shown that coupled-wire constructions allow for an analytically tractable description of integer and fractional, Abelian and non-Abelian topological 2D states. [37][38][39][40][41][42][43][44][45][46][47][48][49] Coupledwire constructions have also led to qualitatively new results, including a classification of interacting topological phases, 50 and the prediction of spontaneously timereversal-symmetry-broken states towards which 2D fractional topological insulators can be unstable.…”
Section: -33mentioning
confidence: 99%
“…35 It has furthermore been shown that also the Chern-Simons term associated with a 2D (fractional) quantum Hall effect is contained in the coupled-wire construction used for the individual building blocks. 47 All of these signatures combined allow to positively identify the gapped phase resulting from the coupling in Eq. (16) as an integer (for m = 0) or fractional (for integer m > 0) quantum Hall state.…”
Section: A Luttinger Liquid Description Of An Individual Building Blmentioning
confidence: 99%